Self-Regulation Based on the Meaning of Life and Its Effects on the Psychological Well-Being of Nursing Student Facing A Quarter Life Crisis: A Systematic Review - Hilda Octri Nurahmah; Ah Yusuf; Nuzul Qur’aniati (Indonesian Journal of Global Health Research, 2026)
Quarter-Life Crisis is a psychological crisis period marked by identity confusion, job suitability concerns, social pressures, and relationship challenges. This crisis is influenced by personal and social factors. Failure to pass the identity crisis phase can lead to a quarter-life crisis, which can ultimately worsen self-regulation and impact psychological well-being. This systematic review was conducted to determine how effective self-regulation based on meaning of life and its effects on psychological well-being in nursing student facing a quarter life crisis. The method used was a systematic review sourced from journals searched through the Sage Journals, Science Direct, CINAHL and ProQuest. Included studies (2020–2025). The PICOS framework was used to determine criteria. From this systematic review, of the 1.847 identified articles, ten studies met the criteria for further analysis. This systematic review evaluates the effectiveness of life meaning-based self-regulation on the psychological well-being of nursing students facing a quarter-life crisis. Self-regulation, including emotional regulation, learning motivation, and self-efficacy, plays a crucial role in managing academic stress and clinical practice pressures. Students with a strong understanding of life meaning tend to have better self-regulation and higher psychological well-being. Self-regulation based on the meaning of life effectively enhances psychological well-being in nursing students facing a quarter life crisis. A clear sense of life purpose supports emotional regulation, stress management, and resilience against academic, clinical, and personal pressures during quarter life crisis.